Empowering community at Kampung 1001 Malam through website development - Ragil Tri Atmi; Faisal Fahmi; Yunus Abdul Halim; Yanuar Dwi Kurniawan; Bertha Niken Ayu Pratiwi; Ajeng Mustika Pratiwi; Nur Khalisha Syamsi (Journal of Community Service and Empowerment, 2024)
In the age of information technology, website development has become a crucial solution in empowering communities, and this article highlights the important role that library and information science students play in this endeavour. The focus is on Kampung 1001 Malam Surabaya, specifically on the community that has undergone relocation to Rusunawa Benowo, Pakal. The website developed by these students became a vital communication and information tool for the community. It provides important information about relocation, available resources, community support, and skills that can help them in facing new challenges after relocation. The importance of good interface design in the development of the website is key, as it ensures that users can easily interact with the website and obtain the information they need. In addition, training and mentoring programs are necessary to ensure effective use of the website. Through the socialisation program, the community is given an in-depth understanding of the importance of the website as a communication tool and source of information that can provide significant benefits in their daily lives. All in all, the development of this website helps to improve the welfare of the community, improve the image of their village, and help them overcome the technological challenges that exist in today's digital era.